Eksistensi Relawan Jokowi Dalam Framing Media Daring Kompas.Com dan Detikcom: Analisis Framing Zhongdan Pan dan Gerald M. Kosicki - Khoirul Ramadhan; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Political turmoil ahead of the 2024 election is increasingly being heard. Political elites poured their energy in droves to be able to fight and do anything for their role models, just like Jokowi's volunteers. The public's love for President Joko Widodo's personality should be appreciated. The arrival of Jokowi's volunteers at the Miss Gathering at GBK with the theme of the United Archipelago Movement in November 2022 succeeded in captivating all pairs of eyes throughout Indonesia. The media crew are no exception, taking and framing the moment this time. Various media backgrounds or ideologies are busy wrapping up this grand moment. This is what is called news framing or news frames. In this study, it aims to find out how Jokowi's volunteers exist in the online media Kompas.com and Detikcom. The author uses the Zhongdan Pan and Gerald M. Kosicki framing analysis model in the analysis basis. The author uses the qualitative-descriptive analysis method as a basis for explaining the results of the discussion by showing twenty-five titles in online media Kompas.com and Detikcom for the period November 26-27 2022. There were 9 reports in online media Kompas and 16 reports in Detik media.